Rehabilitation seltener Erkrankungen: Kleingefäßvaskulitis - Gehlen, Martin; Schwarz-Eywill, Michael; Sabrina, Sabrina (Die Rehabilitation, 2019)
Vaskulitiden sind selten, verlaufen jedoch potenziell lebensbedrohlich. Im Gegensatz zu anderen rheumatischen Erkrankungen konnte in den letzten 10 Jahren zwar die Mortalität gesenkt werden, nicht jedoch die Zahl der Erwerbsminderungsrenten und Arbeitsunfähigkeitstage. Ziel dieses Beitrags ist, einen Überblick über die Krankheitsmanifestationen, die sozialmedizinische Bedeutung und die Therapie im Rahmen der Rehabilitation zu geben.Small vessel vasculitis is a potentially life-threatening disease that affects almost every organ system. In contrast to other inflammatory rheumatic diseases, mortality has been reduced in vasculitis in the last decade, but not the number of disability pensions and days off. Central issues today are infections, cardiovascular events, fatigue and reactive depression. Conclusive rehabilitation concepts have not been implemented as consistently as with other inflammatory rheumatic diseases. The rehabilitation of patients should be done in specialized centers. For a socio-medical assessment, a structured ICF-oriented approach is crucial.
Keywords: Vaskulitis; Kleingefäßvaskulitis; Rehabilitation; Schulung